Enhancing primary care support for informal carers: A scoping study with professional stakeholders. (26th November 2019) - Peters, Michele; Rand, Stacey; Fitzpatrick, Ray
Abstract: Informal carers (i.e. people who provide unpaid care to family and/or friends) are crucial in supporting people with long‐term conditions. Caring negatively impacts on carers' health and experiences of health services. Internationally and nationally, policies, legislation, professional guidance and research advocate for health and care services to do more to support carers. This study explored the views of health and social care providers, commissioners and policy makers about the role and scope for strengthening health service support for carers. Twenty‐four semi‐structured interviews, with 25 participants were conducted, audio‐recorded, transcribed verbatim and analysed by thematic analysis. Three main themes emerged: (a) identifying carers, (b) carer support, and (c) assessing and addressing carer needs. Primary care, and other services, were seen as not doing enough for carers but having an important role in identifying and supporting carers. Two issues with carer identification were described, first people not self‐identifying as carers and second most services not being proactive in identifying carers. Participants thought that carer needs should be supported by primary care in collaboration with other health services, social care and the voluntary sector. Concerns were raised about primary care, which is under enormous strain, being asked to take on yet another task. There was a clear message that it was only useful to involve primary care in identifying carers and their needs, if benefit could be achieved through direct benefits such as better provision of support to the carer or indirect benefit such as better recognition of the carer role. This study highlights that more could be done to address carers' needs through primary care in close collaboration with other health and care services. The findings indicate the need for pilots and experiments to develop the evidence base. Given the crucial importance of carers, such studies should be a high priority.